Identification of computation of solar and wind energy potential for off-grid electric motorcycle battery charging stations - Wayan Adiyasa, I.; Mohd Azri Hizami, Rasid; Wayan Warsita, I.; Arifin, Zainal; Dwipayana, Arif Devi; Suteja, Rai Pramesti (Institute of Electrical and Electronics Engineers Inc., 2023)
Transportation is an important necessity for traveling long distances. Today's transportation, such as battery electric vehicles, is a developing technology to reduce fossil fuel consumption and exhaust emissions. In Indonesia, motorbikes are private vehicles owned by every individual. Battery electric motorbikes (BEM) are a type of electric vehicle that is widely used to travel to other places. However, public infrastructure related to battery charging is not yet fully ready. Most of the energy in 2023 will still come from fossil fuel power plants. This condition shows that the source of emissions is moving from roads to power plants and must be changed by using renewable energy sources (RES). The paper shows the identification of the potential for solar and wind energy that can be applied to replace fossil energy. Energy from solar and wind is converted into electrical energy to be used to charge batteries at the BEM. The results of identifying energy potential show the possibility of using photovoltaics (PV) and wind turbines (WT) for the BEM battery charging process. Average daily energy shows production of up to 14,461 kWh/year for solar energy and 8,327 kWh/year for wind energy. The energy produced by RES shows a reduction in CO2 gas emissions of up to 2,560 kg/year.